Exploring Perspectives and Themes for Histories of Records and Archives: The First International Conference on the History of Records and Archives (I-CHORA I) - Craig, Barbara Lazenby; Eppard, Philip B.; MacNeil, Heather (Archivaria, 2006)
This paper explores perspectives and themes for records and archives histories in the context of the first international conference on the history of records and archives (I-CHORA) held in Toronto, October 2003. It addresses the theoretical and historical dimensions of information artefacts as these dimensions relate to the daily work of archival management, directing attention to their synergistic relationships. Many of these connections between the realms of records theory and records history, including ones that are well-recognized and others that have yet to be fully embraced as necessary parts of archival management practices, are discussed with particular reference to the I-CHORA papers and to the contents of Archivaria 60. The perspectives and themes include archives and material literacies, record-making in specific juridical contexts, comparative and case-study methods for use in further research, uses and users over time, and the possibilities for future inter-disciplinary enrichment. RÉSUMÉ Ce texte explore des perspectives et des thèmes pour des histoires de documents et d'archives dans le cadre du premier congrès international sur l'histoire des documents et des archives (I- CHORA), qui s'est déroulé à Toronto en octobre 2003. Il examine les dimensions théoriques et historiques d'artefacts informationnels tels qu'ils se rapportent au travail quotidien de la gestion des archives, tout en mettant l'accent sur leurs relations synergiques. Nombre de ces liens entre les domaines de la théorie et de l'histoire des documents sont pris en considération en se référant aux communications de la I-CHORA et aux articles du numéro 60 d'Archivaria; notamment les liens qui sont déjà bien reconnus mais également ceux qui méritent d'être considérés comme des éléments essentiels aux pratiques de la gestion des archives. Les perspectives et les thèmes incluent l'alphabétisation archivistique et matérielle, la création de documents dans des contextes juridiques spécifiques, les méthodes comparées et d'études de cas pour poursuivre la recherche, l'usage et les usagers avec le temps, et les possibilités de futurs enrichissements interdisciplinaires.